2007
DOI: 10.1109/tnsre.2007.896997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of STN DBS on Rigidity in Parkinson's Disease

Abstract: We quantified the effects of deep brain stimulation (DBS) of the subthalamic nucleus (STN) and medication on Parkinsonian rigidity using an objective measure of work about the elbow joint during a complete cycle of imposed 1-Hz sinusoidal oscillations. Resting and activated rigidity were analyzed in four experimental conditions: 1) off treatment; 2) on DBS; 3) on medication; and 4) on DBS plus medication. Rigidity at the elbow joint was also assessed using the Unified Parkinson's Disease Rating Scale (UPDRS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 45 publications
1
50
0
1
Order By: Relevance
“…For instance, a functional imaging study demonstrated a continuous decline of dopaminergic function in patients with advanced PD after bilateral STN stimulation. 8,15,24,40 One study included in our meta-analysis stated that medication doses were higher after GPi DBS compared with preoperative doses. 53 Our review confirms that STN DBS was more likely to reduce than to increase levels of medications for patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a functional imaging study demonstrated a continuous decline of dopaminergic function in patients with advanced PD after bilateral STN stimulation. 8,15,24,40 One study included in our meta-analysis stated that medication doses were higher after GPi DBS compared with preoperative doses. 53 Our review confirms that STN DBS was more likely to reduce than to increase levels of medications for patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, rigidity was quantified by "work", in which the average work was done by the torque motor over one cycle (Shapiro et al 2007). However, the concept of "work" views the flexion and extension movements as a single system, and strictly speaking, it is different from the sum of the differences of averaged torque values that we extracted.…”
Section: Resultsmentioning
confidence: 99%
“…For example, some speculate that prolonged electrical stimulation "jams" neuronal circuits (Greenberg 2002); however, this explanation is vague from a neurophysiological point of view. Slightly more developed theories (Pollo and Villemure 2007;Shapiro, Vaillancourt et al 2007;Montgomery and Gale 2008) have proposed mechanisms involving "inhibition of synaptic transmission", a.k.a. the neurochemical hypothesis, or "depolarization blockade", a.k.a.…”
Section: Mechanisms Of Stimulationmentioning
confidence: 99%